2014
DOI: 10.1111/1471-0307.12155
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of apple juice beverages containing whey protein isolate or whey protein hydrolysate based on sensory and physicochemical analysis

Abstract: Whey protein isolate (WPI) or its bioactive hydrolysate (WPH) was mixed with apple juice along with sweetener, obtaining a series of beverages with various pH values. Sedimentation of WPI-apple juice and WPH-apple juice beverages was inhibited at pH values of 3.15 and 3.47, respectively. The higher the whey protein content, the more undesirable was the taste of samples. A clearer appearance with smaller particle size was obtained with WPH-apple juice formulations compared to WPI-apple juice formulations at pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…They can be categorized into two basic groups: (i) fortified dairy beverages (including probiotics, prebiotics/fibers, polyphenols, peptides, sterol/stanols, minerals, vitamins, and fish oil); and (ii) whey-based beverages, i.e., dairy-type beverages, thirst-quenching beverages, and fruit juice-type beverages [4]. Specifically, in fruit juice-type beverages, the whey composition [5] is enriched by the nutraceutical compounds of the fruit, increasing the functional value of the final product [4,[6][7][8]].…”
Section: Introductionmentioning
confidence: 99%
“…They can be categorized into two basic groups: (i) fortified dairy beverages (including probiotics, prebiotics/fibers, polyphenols, peptides, sterol/stanols, minerals, vitamins, and fish oil); and (ii) whey-based beverages, i.e., dairy-type beverages, thirst-quenching beverages, and fruit juice-type beverages [4]. Specifically, in fruit juice-type beverages, the whey composition [5] is enriched by the nutraceutical compounds of the fruit, increasing the functional value of the final product [4,[6][7][8]].…”
Section: Introductionmentioning
confidence: 99%
“…Response surface methodology (RSM) is a beneficial tool for optimizing the formulation of new products. It minimizes the number of experimental trials required and defines mathematical models to evaluate the influence of independent variables on the responses of interest (Goudarzi, Madadlou, Mousavi, & Emam‐Djomeh, ). Recently, RSM was successfully employed by Lashkari, Khosrowshahi, Madadlou, and Alizadeh () to optimize the rheological properties of low‐fat Iranian White cheese supplemented with fat replacers.…”
Section: Introductionmentioning
confidence: 99%
“…Ryan et al (2012) also observed that whey protein beverage suffer from precipitation due to aggregation of thermally denatured proteins. Goudarzi et al (2015) reported higher clarity of apple juice beverage fortified with WPH as compared to beverage fortified with WPI at pH values closer to the iso-electric pH of the whey proteins.…”
Section: Introductionmentioning
confidence: 89%